Studi Hadis di Kalangan Orientalis: Sejarah dan Perkembangannya - Tasbih; Syam, Alda; Ahmad, La Ode Ismail (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
nitially, Orientalism was the way Western scholars interpreted the development and progress of Eastern countries, encompassing aspects such as religion, language, culture, history, and others. However, over time, the focus of Orientalists increasingly turned towards the Arab and Islamic world. One area of particular interest in Islamic studies has been the field of Hadith. Many Orientalists, such as Ignaz Goldziher and Joseph Schacht, have been involved in researching Hadith. Goldziher argued that the majority of Hadith cannot be considered entirely as teachings originating directly from the Prophet.